A Comparative Study on Assessment of Pain as an Outcome by Vas Score in Patients of Adhesive Capsulitis Treated by Hydrodilatation with and without Corticosteroids - Kunal.K.Saoji; Vasant Gawande; Tejas Sadavarte; Kiran M Saoji (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Adhesive Capsulitis is a painful condition commonly occurring in middle age group populationand injectable corticosteroids have shown significant improvement in the pain as an outcome variable.Methodology: A prospective study was conducted from June 2010 to June 2012 for a period of 2 year, at atertiary care hospital in central India. Results: The marked difference in pain relief was seen on VAS scaleon pre intervention to follow up of 3rd week. The mean on pre intervention of steroid group was (8.10) whilethat post intervention 3rd week was (4.90). On the same basis, the pre injection mean was (7.55) in salinegroup while post injection 3rd week mean came out to be (5.75). Thus, pain was relieved on injecting bothsolutions. But, more improvement was observed in steroid group than saline group. Conclusion: Intra salinegroup and steroid group analysis revealed a marked improvement in shoulder range of motion and pain reliefon immediate post intervention and follow up in hydro dilatation of steroid group of patients